LIMIT THEOREMS FOR NUMBER OF PARTICLES WHICH EMIGRATED FROM THE SYSTEM - Базилевич, Ірина Богданівна; Якимишин, Христина Михайлівна; Пилипчук, Христина Володимирівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this paper, the limit theorems for the number of emigrated particles for a homogeneous branching process with continuous time, emigration, and migration are proved.